Aksesibilitas Terhadap Informasi Keagamaan Bagi Penyandang Disabilitas Tuna Rungu: Visualisasi Tanda di Lingkungan Pusdai Jawa Barat - Inna Junaenah; Hendy Hermawan; Samodro Samodro; Dante Rigmalia (Badan Strategi Kebijakan Hukum, 2023)
Human rights law encourages the implementation of state obligations by enacting policies that remove accessibility barriers for persons with disabilities, including a guaranteed access to information. Unfortunately, attention and efforts to facilitate the accessibility of people with deaf disabilities are insufficient, especially regarding religious information. The West Java Islamic Da'wah Center (Pusat Dakwah Islam/Pusdai), as one of the social service units within the local government, barely has a systematic policy basis to facilitate access to religious information, particularly for the